Strength and conditioning for combat sports - Parr, D. Y. (The Crowood Press Ltd., 2018)
The role of the strength and conditioning coach for a combat athlete is to perform a needs analysis in which both the fighter as an individual and the sport itself are assessed in order to develop a high-performance programme. This might include plyometrics, speed and agility, endurance and core stability, strength training and nutrition as just some of the pieces of this complex jigsaw. The aim is to increase strength, speed, power, endurance, agility and flexibility.